Processamento do milho ou sorgo em dietas de alto grão, na terminação de bovinos mestiços leiteiros - Moro, Guidiane (2015)
In order to assess the use of high grain diets, corn or sorghum offered as the entire form or ground, the termination in male animals in confinement, crossbred dairy origin, an essay was conducted at the Escola de Medicina Veterinária e Zootecnia (EMVZ) the Universidade Federal do Tocantins (UFT), in the municipality of Araguaína, in the North region of Brazil, between October 2013 and January 2014, lasting 109 days. It was used 28 crossbred steers whole, from crosses of European breeds with zebu breeds, with an average age of 30 months and average weight of 238 ± 6,1 kg. Four treatments were tested: MGI) whole corn; MGM) Grounded Corn; SGI) Whole Sorghum; and SGM) Grounded sorghum. These diets were formulated targeting an average daily weight gain of 1,5 kg/day/animal, with 100 % concentrate, on a dry matter basis. After a period of 109 days, the animals were slaughtered and subsequently to this period, were made evaluations of temperature, pH, carcass conformation, based on muscular expression and physiological maturity, based on ossification of the vertebrae and ribs. The marbling assessments, color and texture of meat were held. Chemical composition of the meat was performed on sample taken from caudal face of the Longissimus dorsi. The steaks were undergone by evaluators trained in sensory analysis panel. It was evaluated the levels of dry matter, crude protein, ether extract, neutral detergent fiber, acid detergent fiber, non-fiber carbohydrate, total carbohydrates and total digestible nutrients, and their respective apparent digestibility. It was also evaluated the total weight gain, average daily gain, feed efficiency and feed conversion. The experiment was conducted as a completely randomized design with the treatments distributed in a factorial arrangement 2 x 2, being used seven replications (animals) per treatment. According to analyzes carried out by this study, it is concluded that the best performances of average daily intake, feed conversion and body condition score were obtained in diets that used kernel of corn in the ground form, while the meat and carcass performance, treatment with sorghum grain in the entire form, obtained better results.